2011
DOI: 10.1074/jbc.m110.196659
|View full text |Cite
|
Sign up to set email alerts
|

Altered Immune Response in Mice Deficient for the G Protein-coupled Receptor GPR34

Abstract: The X-chromosomal GPR34 gene encodes an orphan G i protein-coupled receptor that is highly conserved among vertebrates. To evaluate the physiological relevance of GPR34, we generated a GPR34-deficient mouse line. GPR34-deficient mice were vital, reproduced normally, and showed no gross abnormalities in anatomical, histological, laboratory chemistry, or behavioral investigations under standard housing. Because GPR34 is highly expressed in mononuclear cells of the immune system, mice were specifically tested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 59 publications
5
103
0
Order By: Relevance
“…Only nine genes were differentially expressed in the cortex of mutant KI mice; Camkk1, Cort, Ctxn3, Gli3, Gpr23, Gpr34, Lsm10, Tnnc1, and Tom1l2. Differential expression of cortical Camkk1, Gpr34, Tom1l2, and Cort gives an indication for an immune-related component, as these genes seem involved in the immune response (17)(18)(19)(20)(21).…”
Section: à3mentioning
confidence: 99%
“…Only nine genes were differentially expressed in the cortex of mutant KI mice; Camkk1, Cort, Ctxn3, Gli3, Gpr23, Gpr34, Lsm10, Tnnc1, and Tom1l2. Differential expression of cortical Camkk1, Gpr34, Tom1l2, and Cort gives an indication for an immune-related component, as these genes seem involved in the immune response (17)(18)(19)(20)(21).…”
Section: à3mentioning
confidence: 99%
“…However, as stated above, LPT, a potent inducer of mast cell degranulation, did not activate GPR34 ( 22 ). In addition, peritoneal mast cells from GPR34-defi cient mice still responded to LysoPS ( 41 ). Thus, it is likely that GPR34 is not involved in the mast cell degranulation response induced by LysoPS.…”
Section: Gpr34/lpsmentioning
confidence: 77%
“…Because GPR34 is highly expressed in mononuclear cells of the immune system, LysoPS appears to serve as an immunomodulator through GPR34 in response to immunological challenges. Further studies are needed to elucidate the Liebscher et al ( 41 ) demonstrated that GPR34 from carp, a kind of fi sh, did react strongly with LysoPS . On the other hand, the result of the initial study by Sugo et al ( 35 ) was confi rmed by Kitamura et al ( 42 ), in which activation of GPR34 was evaluated by a Ca 2+ mobilization assay and by a newly developed transforming growth factor (TGF) ␣ shedding assay.…”
Section: Gpr34/lpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether GPR34 activates NF-kB is unknown. Knock-out studies in mice revealed a physiological role for GPR34 in the immune response 7 which is tightly regulated by NF-kB. To examine the role for GPR34 in NF-kB activation, we over-expressed GPR34 in the B-cell lymphoma cell line BJAB, in which the NF-kB pathway is relatively quiescent.…”
Section: Resultsmentioning
confidence: 99%